Two librarians, an archivist, and 13,000 images: collaborating to build a digital collection - Oehlerts, Beth, author; Legg, Kathleen, author; Hunter, Nancy Chaffin, author; The University of Chicago, publisher (Colorado State University. Libraries, 2010)
Colorado State University Libraries has been creating digitized collections, primarily from its Archives and Special Collections unit, since 2000. These projects involved collaboration among Archives, Cataloging, and Digitization; the most recent and ambitious project, digitizing 13,000 historical images of the university dating from the 1880s into the 1930s, required closer collaboration than any previous project. The three authors, each with a distinctive role in the project, use this case study to illustrate and discuss in detail the different professional and technical skills and perspectives that each brought to the project and how they learned from each other. The authors present lessons learned in how to effectively build successful internal partnerships to further digitization projects.
Keywords: digital collections; historical images; digitization projects; Colorado State University Libraries